2017
DOI: 10.1056/nejmoa1613792
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical or Biologic Prostheses for Aortic-Valve and Mitral-Valve Replacement

Abstract: The long-term mortality benefit that was associated with a mechanical prosthesis, as compared with a biologic prosthesis, persisted until 70 years of age among patients undergoing mitral-valve replacement and until 55 years of age among those undergoing aortic-valve replacement. (Funded by the National Institutes of Health and the Agency for Healthcare Research and Quality.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
369
5
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(402 citation statements)
references
References 26 publications
10
369
5
18
Order By: Relevance
“…For patients >70 years old, the guidelines consider it is reasonable to use a bioprosthesis for SAVR, whereas between 50 and 70 years old, the choice between mechanical versus bioprosthetic valve should be individualised. Compared with mechanical valves, bioprostheses present the advantage of not requiring lifetime anticoagulation and a recent study reported that, among patients older than 55 years, survival is similar with bioprosthetic versus mechanical valves 5. However, the main limitation of bioprostheses is their limited durability, which exposes the patient to the risk of aortic valve reintervention.…”
Section: Introductionmentioning
confidence: 99%
“…For patients >70 years old, the guidelines consider it is reasonable to use a bioprosthesis for SAVR, whereas between 50 and 70 years old, the choice between mechanical versus bioprosthetic valve should be individualised. Compared with mechanical valves, bioprostheses present the advantage of not requiring lifetime anticoagulation and a recent study reported that, among patients older than 55 years, survival is similar with bioprosthetic versus mechanical valves 5. However, the main limitation of bioprostheses is their limited durability, which exposes the patient to the risk of aortic valve reintervention.…”
Section: Introductionmentioning
confidence: 99%
“…While bAVR is an attractive option in the short term, SVD is inevitable, particularly after the first decade of implantation . Mechanical AVR (mAVR) has the distinct advantage of long‐term durability; however, postoperative bleeding events and readmission for bleeding have long been considered the principal disadvantage of mAVR . However, this is not a universal finding and prior studies of bleeding events have demonstrated conflicting results .…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, otros trabajos fueron discordantes con estos resultados (1,5,9) . En una revisión sistemáti-ca publicada en el European Heart Journal en 2017 se examinaron trabajos que comparaban el uso de bioprótesis aórtica versus mecánica (mediante pareamiento de propensión o con análisis multivariable) y se encontraron resultados similares entre los dos tipos de prótesis, pero los resultados fueron levemente más favorables para la válvula mecánica en el grupo de pacientes más jóvenes (5) .…”
Section: Discussionunclassified
“…En una revisión sistemáti-ca publicada en el European Heart Journal en 2017 se examinaron trabajos que comparaban el uso de bioprótesis aórtica versus mecánica (mediante pareamiento de propensión o con análisis multivariable) y se encontraron resultados similares entre los dos tipos de prótesis, pero los resultados fueron levemente más favorables para la válvula mecánica en el grupo de pacientes más jóvenes (5) . A la par de esto, en un trabajo publicado muy recientemente en New England Journal of Medicine (9) aórtica aumentó significativamente (de 11,5% a 51,6%). Además, se encontró que la mortalidad a 15 años fue significativamente mayor en bioprótesis aórtica que en válvula mecánica en los pacientes de 45 a 54 años (HR 1,23, p=0,03), pero no en aquellos de 55 a 64 años (HR 1,04, p=0,60).…”
Section: Discussionunclassified
See 1 more Smart Citation